A Model of Rat Thrombocytopenia Induced by Cyclophosphamide - Kristiana, Hery; Nailufar, Florensia; Winoto, Imelda L; Tjandrawinata, Raymond R (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X)
This study is aimed at optimizing the dose of cyclophosphamide in thrombocytopenia rat model. A suitable drug dosage that coulds induce thrombocytopenia rat model. A suitable drug dosage that could induce thrombocytopenia in rat was then investigated. Animal model of 25 rats were randomly divided into five groups: Normal (group A), Cyclophosphamide low dose (group B), medium dose (group C), high dose (group D), very high dose (group E) with each of 5 rats. The four dosage groups were given 25, 50, 100, 150 mg/kg BW cyclophosphamide, respectively. Cyclophosphamide was given by subcutaneous injection once a day for 3 consecutive days. All groups were under investigation for 8 days. The result suggested that a decrease in the platelet count, white blood cell, and mean corpuscular volume of all group cyclophosphamide induced at the 7th day were significantly different than that of Normal. The platelets count was reduced but fluctuated greatly, all of the rats dies in group E at 7th day and group D at 8th day. Though all 4 dosages successfully initiated thrombocytopenia as the platelets number dorpped at the 7th day, the low dose was considered to be a suitable one that was of high efficacy and low toxicity. Thus, using Wistar rats challenged by subcutaneous injection of cyclophosphamide 25 mg/kg per day for 3 consecutive days showed one simple, feasible and stable rat thrombocytopenia model that could be used for phamacodynamic test of the drugs which are supposed to have platelet increasing effect. Keywords : rat, thrombocytopenia, cyclophosphamide